Application of nursing consultation in special outpatient service (护理咨询在特需门诊服务中的应用) - ZHANG Yongli (张永丽); MI Wei (米薇); SHU Baozhen (舒宝珍); YU Lei (于蕾); XING Hui (兴慧); WANG Jing (王静) (中西医结合护理)
Objective To improve the application effect of nursing consultation in special outpatient service, so as to further improve the patient revisits rate, appointment rate and satisfaction degree. Methods From March to August 2021, hospital had set up nursing consultation in special outpatient services. Indicators of patient revisits and appointment were monitored before and after the implementation of nursing consultation, and the basic information of patients one week before and after the implementation were retrospectively analyzed. Results After the implementation of nursing consultation, the number of patient revisits, appointments and satisfaction rate were 57. 07 %, 70. 57 % and 100 % respectively, which were significantly higher than those before the implementation of nursing consultation(P＜0. 01). The time of consultation and guidance was significantly shortened (P＜0. 01). After the implementation of nursing consultation, the number of patients who visited to various departments, with different age groups and different educational levels were increased. Conclusion Setting up nursing consultation in special outpatient service can improve the quality of nursing, increase the number of appointments and follow-up visits and helps to improve the disease awareness of patients with different ages and different educational levels. (目的 提高护理咨询在特需门诊服务中的应用效果, 从而进一步提高患者复诊量、预约量及满意度。方法 医院2021年3月—8月在特需门诊服务中设置护理咨询, 对实施护理咨询前后工作指标情况进行总结, 并对实施前后1周患者基本信息情况进行统计分析。结果 实施护理咨询后就诊量、预约量、满意度分别57. 07%、70. 57%和100. 00%, 与未增设护理咨询前相比提高(P＜0. 01), 咨询指导时间明显缩短(P＜0. 01), 就诊效率提升, 并且实施护理咨询后各科室、不同年龄段及不同文化程度人群就诊量均有增加。结论 在特需门诊服务中设置护理咨询, 能够改善门诊护理服务质量, 可提升预约量与复诊量, 对提升不同年龄段及不同文化程度患者对疾病的了解程度具有积极意义。)